Evidence for the decay X(3872) → [psi](2S)[gamma] - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Nuclear physics. B, Particle physics, 2014)
Evidence for the decay mode X(3872)→ψ(2S)γ in B+→X(3872)K+ decays is found with a significance of 4.4 standard deviations. The analysis is based on a data sample of proton-proton collisions, corresponding to an integrated luminosity of 3 fb−1, collected with the LHCb detector, at centre-of-mass energies of 7 and 8 TeV. The ratio of the branching fraction of the X(3872)→ψ(2S)γ decay to that of the X(3872)→J/ψγ decay is measured to beB(X(3872)→ψ(2S)γ)B(X(3872)→J/ψγ)=2.46±0.64±0.29, where the first uncertainty is statistical and the second is systematic. The measured value does not support a pure DD¯⁎ molecular interpretation of the X(3872) state.